Persepsi Mahasiswa terhadap Program PPG (Studi pada Mahasiswa Program Studi Pendidikan Ekonomi FKIP Unpatti Angkatan 2018–2020) - Martatik, Siti; Salong, Amjad; Ubra, Franklin William (Universitas Pattimura, 2022)
Regulatory changes regarding the Teacher Professional Education (PPG) program have generated diverse perceptions among education students, particularly those from LPTK institutions. This study aims to explore the perceptions of students in the Economics Education Study Program at the Faculty of Teacher Training and Education, Pattimura University, concerning the PPG program. Employing a descriptive qualitative approach, data were collected through in-depth interviews and documentation involving 30 respondents. The findings indicate that most students have a good understanding of PPG and express a strong interest in participating. However, concerns arise regarding government policies that allow non-education graduates to obtain teacher certification, which is perceived to create disparities in competence and professional competition. The study highlights the urgency of enhancing information dissemination, ensuring policy fairness, and improving program-level access. Strategic efforts are required from institutions and policymakers to refine the implementation of PPG so that it not only produces professional teachers but also maintains academic justice. Recommendations include strengthening internal campus outreach, developing adaptive information systems for PPG, and harmonizing inter-institutional education policies